Cranial Biometrics of the Iberian Myotis myotis/Myotis blythii Complex: New Data for Studying the Fossil Record - Galán, Julia (2018)
The Myotis myotis/M. blythii species complex, spread across the Western Palearctic, is a problematic group for which the taxonomy of the species is not yet satisfactorily resolved. The Iberian Peninsula played a key role in its evolutionary history as a Pleistocene refuge and as the starting point for the eastward expansion of M. myotis in the early Holocene, while M. blythii reached the Iberian Peninsula only during the middle Holocene. The study of Iberian populations and particularly of the Iberian fossil record is of high interest in this regard. However, there are few data available on the biometry of the skulls and teeth of Iberian populations (which differ somewhat in size from those of other regions of Europe and Asia) or tools for the identification of fragmentary cranial remains. Much of the Quaternary Iberian record of large Myotis remains unassigned. Here, we contribute to the task of determining fragmentary cranial remains by providing new cranial and dental biometric data from extant Iberian populations, predictive models for isolated upper molar identification, and a set of indices that allow quantitative evaluation of the differences in anatomical traits (in skull and molars) between the two species.